Evolutionary Biology and Classical Teleological Arguments for God's Existence - Rooney, James Dominic (Heythrop journal, 2013)
Much has been made of how Darwinian thinking destroyed proofs for the existence of God from ‘design’ in the universe. I challenge that prevailing view by looking closely at classical ‘teleological’ arguments for the existence of God. One version championed by Aristotle and Thomas Aquinas stems from how chance is not a sufficient kind of ultimate explanation of the universe. In the course of constructing this argument, I argue that the classical understanding of teleology is no less necessary in modern Darwinian biology than it was in Aristotle's time. In fact, modern biology strengthens the claims that teleological arguments make by vindicating many of their key features. As a consequence, I show how Aristotle and Aquinas' teleological argument for an intelligent First Cause remains valid.